329 Severe Retinopathy of Prematurity (ROP) Remains a Marker of Childhood Disabilities: Results from the Caffeine for Apnea of Prematurity Trial. (October 2012) - Schmidt, B; Davis, P; Doyle, L; Anderson, P; Asztalos, E; Solimano, A; Grunau, R; Ohlsson, A; Dewey, D; Moddemann, D; Barrington, K; Tin, W; et al.
Abstract : Background: The Cryotherapy for Retinopathy of Prematurity Cooperative Group showed that the severity of ROP was a marker for functional disability at 5.5 years in infants ≤1250 g BW who were born in the late 1980s. Objective: To determine whether severe ROP remains a strong predictor of visual and non-visual disabilities at age 5 years in infants ≤1250 g BW who were enrolled in the CAP trial between 1999 and 2004. Methods: 5-year follow up of 1580 surviving CAP children with known ROP status. Severe ROP was defined as stage 4 or 5 disease or receipt of retinal therapy in at least one eye. Outcomes were disabilities in 6 domains, and including cognitive impairment (Full Scale IQ< 70), motor impairment (GMFCS level 2–5), deafness and blindness. Odds ratios were adjusted for antenatal steroids, gestational age, sex, multiple birth, and mother's education. Results: There were 94 survivors with and 1486 without severe ROP. Rates of visual and non-visual disabilitites were significantly higher in children with severe ROP (Table 1 ). Conclusions: Severe ROP remains a strong marker of childhood disabilities in a recent and large international cohort of infants ≤1250 g BW.